Kaidah Lā Ḍarar wa Lā Ḍirār sebagai Instrumen Normatif dalam Pembatasan Pemanfaatan Sumber Daya Alam - Upi Sopiah Ahmad; Mhd Yadi Harahap; Sukiati Sugiono; Nurasiah Nurasiah (Irsyaduna: Jurnal Studi Kemahasiswaaan, 2025)
The utilization of natural resources in Islamic law is fundamentally permissible; however, it is neither absolute nor value-free. Such utilization is subject to Sharīʿah principles aimed at safeguarding human well-being and environmental sustainability. This article examines the position of the fiqh maxim lā ḍarar wa lā ḍirār as a normative instrument for determining the permissible limits of natural resource utilization within Islamic law. The study employs a normative legal research method with conceptual and philosophical approaches, analyzing fiqh maxims, maqāṣid al-sharīʿah, and both classical and contemporary literature on Islamic environmental jurisprudence. The findings demonstrate that the maxim lā ḍarar wa lā ḍirār functions not merely as an ethical principle or moral prohibition, but as an operational legal tool capable of determining changes in legal status. Activities related to natural resource utilization that are initially deemed permissible (mubāḥ) may be restricted or prohibited when they are proven, or reasonably expected, to cause significant harm, including ecological degradation, threats to public safety, and long-term environmental impacts of a collective and sustainable nature. This study further emphasizes that the contemporary expansion of the concept of harm encompasses ecological dimensions and future risks, thereby positioning preventive measures as a central principle in Islamic legal reasoning. This article contributes conceptually by positioning the maxim lā ḍarar wa lā ḍirār as a normative parameter in the development of Islamic environmental jurisprudence and as a Sharīʿah-based justification for regulating natural resource utilization in pursuit of public interest and environmental sustainability.